Factors associated with alkali production from arginine in dental biofilms - Huang, X; Exterkate, R A M; ten Cate, J M (Journal of dental research, 2012)
Alkali production by oral bacteria in the oral cavity has been linked to protection against dental caries. The current study assessed various parameters associated with ammonium produced during arginine catabolism in dental biofilms. Polymicrobial biofilms were formed with saliva as the inoculum. The NH(3) level and the pH of the spent medium were used to monitor and quantitate the bacterial reactions. The presence of sucrose, a low buffer capacity, and a low pH (≤ pH 4.5) were found to hamper alkali production from arginine. The rate of alkali production exhibited an optimum around pH 5.5. Biofilms were found to produce NH(3) also from polypeptides and proteins in the medium. The biofilm age affected these processes. The experimental model proved valuable for the assessment of the collective bacterial reactions determining the overall pH outcome. This experimental approach could bridge the gap in our knowledge between pH-rise phenomena and caries susceptibility from clinical observations and studies performed on alkali-producing bacteria in well- controlled, though simplified, in vitro models. Analysis of our data supports the hypothesis that the initiation and progression of dental caries may be influenced by the relative rates of acid and base formation, which critically depend on the aforementioned parameters.